Effectiveness of Canva-Based Interactive Animation Media in Enhancing Learning Interest of Second-Grade Madrasah Ibtidaiyah Students - Fitriyah, Raudhatul; Hilmiyati, Fitri; Juhji, Juhji (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This research is motivated by the low interest of students in learning the material 'The Word of Invitation and the Word of Refusal', which indicates the need for a method that can be used to improve the learning process. The Word of Invitation and the Word of Refusal' which indicates the need for a more effective learning method. This study aims to analyze the Effect of Canva-based interactive animation media on the interest of 2nd-grade students at Madrasah Ibtidaiyah Masarratul Muta'allimin in Banten Province. A quasi-experimental design involved 56 students divided into experimental and control groups. Student interest data were collected through questionnaires and analyzed using normality, homogeneity, and t-tests. The t-test results indicated a significant difference between the two groups, with a t value of -27.117 (p = 0.000) and an average difference of 19.036. These results suggest that Canva-based interactive media significantly enhances students' interest in learning compared to conventional methods. Canva-based interactive media can effectively increase student engagement. Recommendations for educational practice include integrating interactive media into classroom learning to boost student involvement. Further research is recommended to explore the long-term impact of this media on students' academic performance.